PENGARUH VARIASI MASSA REFRIGERAN R410A PADA SISI LOW STAGE TERHADAP KINERJA MESIN PENDINGIN CASCADE - Muhammad Hasan Basri; Mustafa Mustafa; Khairil Anwar (Jurnal MEKANIKAL, 2014)
Abtract: The effect of R410 Refrigerant Mass Variation of The Low Stage Side on Performance of Cascade Engine Cooling. The aim of this research is to determine the effect of changes in the mass variation of refrigerant R410A in the Low - Stage Cooling on the coeficient of performance of the cascade refrigeration. The benefits of this research is to contribute valuable knowledge in the field of refrigeration, especially in the areas of health, agriculture and fisheries. The research method used is to perform testing or direct observation of the cascade refrigeration by replacing the stuffing or the mass of refrigerant in the low - stage of cascade system. Variation of refrigerant mass is 180, 190 and 200 gram. Any variations were observed mass of the pressure and temperature at a predetermined test points. The results showed that at the same time the rising in cooling capacity of the machine cascade with increasing refrigerant mass speed. With a mass of 180 gram showed a significant increase in weight compared to other masses, where a higher cooling capacity kW at 0.39 and coefficient of performance is 1.23.   Keywords :  Mesin refrigerasi, cascade, refrigeran R410A